The Effect Of Classroom Management, Digital Literacy And School Environment Quality On Educational Service Quality In Higher Education Institutions - Wariunsora, Marlen; Subroto, Desty Endrawati; Haribowo, Rio; Ramli, Akhmad; Nugroho, Isfauzi Hadi; Sujatmiko, Wandi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The research study examines how classroom management practices together with digital literacy skills together with school environmental conditions create an effect on educational service delivery at higher education institutions. The research background establishes the need for higher education service improvement because of international competition and educational digital transformation. The researchers conducted their study through a quantitative explanatory approach which used survey data collected from 200 active students who were selected through purposive sampling. The researchers performed data analysis through multiple linear regression after they established both validity and reliability and validated their classical assumptions. The study results show that educational service quality benefits from classroom management practices and digital literacy skills and school environmental conditions which create positive substantial effects. The study presents theoretical contributions which enhance research on educational management and higher education service quality through its empirical demonstration of factors that determine educational service quality. The research findings provide higher education institution managers with strategic guidance which they can apply to create policies and practices that will improve learning together with educational technology and campus environment management, thus enhancing educational services.